Exploration and respectation of the spatial structure of cities, towns, townships and villages as a significant formant of their identity - Dringelis, Liucijus; Ramanauskas, Evaldas; Povilaitienė, Ingrida; Mačiukėnaitė, Justina (Journal of Architecture and Urbanism, 2015)
Under the conditions of globalization and integration the issue of identity preservation with respect to the spatial structure of the Lithuanian cities, towns, townships and villages has been discussed by many authors. The need to protect the originality and identity of landscape in the countries of the world, their natural and cultural heritage, the spatial structure and architecture of the cities, towns, townships and villages under such complicated circumstances is considered in a number of national and international documents. On the basis of the carried out indoor research and field exploration the paper aims at the discussion of the most significant urbanistic, architectural, landscape and other features that form the specificity and identity of the Lithuanian cities, towns, townships and villages. The following specific features of the settlements have been analysed: the period when a settlement emerged, its visual interaction with the environment (panoramas, silhouettes), natural conditions (terrain line, water bodies, green spaces), plan and spatial structure (street network, building arrangement, squares, green spaces, etc.) and significant buildings (sacred, public and other buildings and constructions). Due to their significance and uniqueness all the mentioned features form the identity of the analysed object. The following objects were selected for the research: all towns (103), townships (249), church villages (301), villages as local administrative centres (97) and ordinary villages with adequate natural and cultural heritage (318), in all 1.068 settlements, or 5% from the total number of the country’s settlements (21.043). On the basis of the carried out research, the paper analyses the historical development of Lithuanian cities, towns, townships and villages; the current demographical and urban status of the country’s settlement system; defines the principles of settlement selection and identity research methods; discusses the research progress and the results obtained during the exploration of the specificity of the spatial structure of cities, towns, townships and villages. The analysis of the spatial structure of the country’s largest cities has also been presented which reveals the violations of their most specific features (e.g. old towns, river valleys, etc.). The paper also offers a comparative analysis of the specificity of Lithuanian cities, towns, townships and villages and adequate types of settlements in foreign countries.